Penilaian Kepuasan Pengguna pada Aplikasi E-Wallet Menggunakan Metode AHP (Analytical Hierearchy Process): Studi Kasus pada Mahasiswa D3 Sistem Informasi Akuntansi Telkom University - Marcela Daruwati; Rahmadi Rahmadi; Irman Hariman (Riviera Publishing, 2025)
The development of financial technology has driven an increase in the use of digital wallets (e-wallets). However, society still faces difficulties in determining the most suitable e-wallet application due to the absence of an objective evaluation system. This study aims to compare three e-wallet services —namely, OVO, ShopeePay, and DANA —and provide information that can strengthen user confidence in choosing these services. The research method employed is the Analytical Hierarchy Process (AHP), with data obtained through a Google Form questionnaire. The analysis focuses on three main aspects: transaction speed, security, and user interface/user experience (UI/UX). The findings reveal that ShopeePay is the most preferred e-wallet compared to OVO and DANA. These results can help users select the most suitable e-wallet for their needs, as well as provide valuable input for developers to enhance service quality